Pengaruh Harga dan Kualitas Produk terhadap Keputusan Pembelian Laptop Merek Hp di Sampit - Dewi, Rusmila; Putra, Dwi Ardi Wicaksana (Keizai, 2020)
This study aims to determine whether the price and quality of products affect the purchasing decisions of HP brand laptops in Sampit. This research population is a Sampit community that will make a purchase and have used the HP14 BS702 TU brand laptop before. The samples taken were 60 respondents using the Accidental Sampling method where the sampling method was based on coincidence and was considered by the researcher to be suitable. The regression used is logistic regression. Based on statistical data analysis, the indicators in this study are valid and the variables are reliable. The results of this study indicate that in terms of price and product quality have a significant positive effect on purchasing decisions.